PENGARUH KEPEMIMPINAN, MOTIVASI DAN PELATIHAN TERHADAP KINERJA PEGAWAI (Studi pada Perusahaan Daerah Air Minum Kota Kendal) - Dhevi Ayuning Tesiana, 09.05.51.0072; Astuti, Sih Darmi (Students Journal of Economic and Management, 2013)
This study aims to examine and analyze the effect of leadership, motivation and training ofemployees in the performance of the Regional Water Company Kendal Town. Data collectionwas done through questionnaires and carried on at 108 Regional Water Company employeeKendal Town.In this case, the researchers did not use a sampling technique, as is the method used censusdata and testing techniques used in this research include testing the validity of using the KaiserMayer Olkin Measure of Sampling Adequacy (KMO) qualified for further analysis usingmultiple regression analysis to explain the relationship between these variables.The result is a hypotesis that shows leadership and the stongest positive influence onemployee performance, followed by training and motivation on employee performance.Keywords: Leadership, motivation, training and Employee Performance.